2006
DOI: 10.1111/j.1365-2028.2006.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevational variation in diversity and composition of land‐snail faunas in a Tanzanian forest

Abstract: We sampled terrestrial molluscs at fifteen elevations between 400 and 2000 m in Mwanihana Forest Reserve, Tanzania and recorded 84 taxa. Four diversity measures – species density (DP), species richness (D20) and observed (SO) and interpolated (SI) alpha diversity – were measured; beta diversity and abundance were also investigated. Mean elevational range was 470 m. DP, D20, alpha diversity and mollusc abundance increased with elevation, but alpha diversity peaked at 1695 m (SO) or 1500 m (SI) and declined at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
17
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
5
17
0
1
Order By: Relevance
“…Moist conditions are necessary for land-snail respiration and reproduction (Coney et al, 1982) and for the production of mucus, which is vital for locomotion (Cameron, 1970). Our results agree with Boycott's (1934) pioneering work on land snails as well as with studies carried out over the last decade in several countries (Millar and Waite, 2002;Martin and Sommer, 2004;Tattersfield et al, 2006;Horsák et al, 2007). According to Emberton et al (1999) snail diversity can be explained by the increased humidity of the environment.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moist conditions are necessary for land-snail respiration and reproduction (Coney et al, 1982) and for the production of mucus, which is vital for locomotion (Cameron, 1970). Our results agree with Boycott's (1934) pioneering work on land snails as well as with studies carried out over the last decade in several countries (Millar and Waite, 2002;Martin and Sommer, 2004;Tattersfield et al, 2006;Horsák et al, 2007). According to Emberton et al (1999) snail diversity can be explained by the increased humidity of the environment.…”
Section: Discussionsupporting
confidence: 82%
“…Although the land snails account for a significant component of faunistic endemism in this region, it has been poorly studied (Thomé et al, 2006). Our study attempted to address this gap in knowledge by investigating the relationship between species composition and the environmental variation for the land snails of two hillsides on Ilha Grande (Angra dos Reis, Rio de Janeiro), which forms part of the Atlantic Rain Forest.…”
Section: Introductionmentioning
confidence: 99%
“…Both species richness and snail abundance declined with increasing elevation in afromontane forests on Mount Kenya (Tattersfi eld et al 2001). In contrast, species richness peaked at intermediate elevation in Tanzanian forests (Tattersfi eld et al 2006). In contrast, species richness peaked at intermediate elevation in Tanzanian forests (Tattersfi eld et al 2006).…”
mentioning
confidence: 96%
“…Similarly, species density (number of species per sampling plot) declined with elevation on Mount Kinabalu and Mount Tabuyukon in Malaysian Borneo (Liew et al 2010) and on calcareous mountains in southeastern France (Aubry et al 2005). It has been suggested that community overlap causes the hump-shaped relationship between diversity and elevation (Tattersfi eld et al 2006). It has been suggested that community overlap causes the hump-shaped relationship between diversity and elevation (Tattersfi eld et al 2006).…”
mentioning
confidence: 99%
“…Este valor es inferior al observado en algunas otras regiones del mundo, seguramente de mayor área, como el archipiélago hawaiano en el que se distribuyen 750 especies (Cowie 1995) (Wardhaugh 1996), a las 82 especies del sur de la península de Michigan (Nekola 2004), y a las 84 especies provenientes de los bosques de Tanzania (Tattersfield et al 2006). Hasta el momento, el de viñales es el mayor valor de riqueza de especies detectado a escala regional en el archipiélago cubano, superior a las 86 especies de moluscos terrestres observadas por Jaume (1972) en la región de Sierra del Rosario.…”
Section: Jeanneretia Modicaunclassified